ANALISIS PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA MELALUI KOMPENSASI SEBAGAI VARIABEL INTERVENING (Survei pada Karyawan PT Wahana Sun Solo) - Y. Djoko Suseno, Sunu Waskito Aji, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The high performance of the employee is leadership, competency andcompensation is a factor in improving employee performance in a company.Good performance improvements will make progress for the company, sothat planned goals can be achieved. The purpose of this research is to knowthe significance of leadership influence and competence toward employeeperformance through compensation as intervening variable at PT WahanaSun Solo.Keywords: Leadership, Competence, Compensation and Performance